Neuroergonomic and psychometric evaluation of full-face crew oxygen masks respiratory tolerance: a proof-of-concept study. Issue 5 (9th November 2018) - Nierat, Marie-Cécile; Raux, M; Redolfi, S; Gonzalez-Bermejo, J; Biondi, G; Straus, C; Rivals, I; Morélot-Panzini, C; Similowski, T
Abstract : Introduction: Preventing in-flight hypoxia in pilots is typically achieved by wearing oxygen masks. These masks must be as comfortable as possible to allow prolonged and repeated use. The consequences of mask-induced facial contact pressure have been extensively studied, but little is known about mask-induced breathing discomfort. Because breathlessness is a strong distractor and engages cerebral resources, it could negatively impact flying performances. Methods: Seventeen volunteers (age 20–32) rated respiratory discomfort while breathing with no mask and with two models of quick-donning full-face crew oxygen masks with regulators (mask A, mask B). Electroencephalographic recordings were performed to detect a putative respiratory-related cortical activation in response to inspiratory constraint (experiment 1, n=10). Oxygen consumption was measured using indirect calorimetry (experiment 2, n=10). Results: With mask B, mild respiratory discomfort was reported significantly more frequently than with no mask or mask A (experiment 1: median respiratory discomfort on visual analogue scale 0.9 cm (0.5–1.4), experiment 1; experiment 2: 2 cm (1.7–2.9)). Respiratory-related cortical activation was present in 1/10 subjects with no mask, 1/10 with mask A and 6/10 with mask B (significantly more frequently with mask B). Breathing pattern, sigh frequency and oxygen consumption were not different. Conclusions: In a laboratory setting, breathing through high-end aeronautical full-face crew oxygen masks can induce mild breathing discomfort and activate respiratory-related cortical networks. Whether or not this can occur in real-life conditions and have operational consequences remains to be investigated. Meanwhile, respiratory psychometric and neuroergonomic approaches could be worth integrating to masks development and evaluation processes.